Category psychosocial development in modern psychology - Shamne, A. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2017)
In the article is analyzed the meaning, content and especially of the concept using of psychosocial development in domestic and western psychology. It represents a balanced combination of socialization and personalization processes, integration of the two development's processes – development of personality as appropriation of social experience and the subject's development as personal disclosure of myself. Psychosocial development is presented as part of the model of age's analysis in different concepts of development. It is shown its relationship with the network of related concepts, such as: psychosocial personality, psychosocial attitude, psychosocial conflict, psychosocial crisis, psychosocial identity, psychosocial motive, psychosocial maturity and psychosocial maturation and others. It is presented the following aspects of research of psychosocial development: psychosocial characteristics of different social and age groups, normativity – not normativity of development (problem of psychosocial deviations); ontogenesis – dysontogenesis, psychosocial factors of development (family, interpersonal, personal, etc.), psychosocial support and rehabilitation of the individual. It is concluded that concept of psychosocial development integrates concepts network, in which is emphasized the importance of interaction between person (man) and society, the individual and social in the individual development. It is presented the results of empirical operationalization of the phenomenon of psychosocial development.
Keywords: сategory; psychosocial development; personality; functional dichotomies; socialization; individualization